Identification And Characterization Of Colletotrichum Spp. From Anthracnose Of Guava (Psidium Guajava) And Banana (Musa Spp.), And Gliocephalotrichum Spp. From Fruit Rot Of Rambutan (Nephelium Lappaceum) - Anuar, Intan Sakinah Mohd (2013)
Fruit crops are vulnerable to postharvest diseases causing severe losses and among the most common postharvest diseases are anthracnose and fruit rot. Studies on postharvest disease on three fruit crops, namely guava (Psidium guajava), banana (Musa spp.) and rambutan (Nephelium lappaceum) were conducted. From guava and banana, anthracnose disease was observed, and two species of Colletotrichum were identified. Based on morphological characteristics of colony colours, conidia, appressoria and presence or absence of setae, the two species of Colletotrichum were identified as C. gloeosporioides (52 isolates) and C. musae (six isolates). For confirmation of species and phylogenetic analysis, sequencing of Internal Transcribed Spacer (ITS) regions and ß-tubulin gene were applied. However, based on BLAST results, 55 isolates were identified as C. gloeosporioides and only three isolates were identified as C. musae. Phylogenetic analysis using ITS regions and ß-tubulin gene sequences based on individual and combine datasets using Neighbour-joining (NJ) and Maximum likelihood (ML) methods showed that C. gloeosporioides and C. musae were clearly separated into different clades.